Determination of partial conductivities and electrolytic domain of yttrium-doped zirconia prepared from Indonesian zircon sand - Kim I.-H.; Singh B.; Lim J.-W.; Song S.-J. (My University, 2025)
In this work, yttrium stabilized zirconia (YSZ) was synthesized using zirconium oxychloride (ZOC) which was extracted from high-grade zircon sand mine in Indonesia. The ZOC was extracted from the zircon sand by caustic fusion method which was used to prepare 8 mole% yttrium doped zirconia (YSZ8) powder with average particle diameter of 422 nm by co-precipitation method. The powder was then granulated to ~15 μm granules by spray drying process and the granules were used to fabricate dense sintered body. The sintering temperature of 1600 °C was determined by monitoring the relative shrinkage rate with temperature.<ed-check the technical meaning> The prepared materials were analyzed by X-ray diffraction (XRD), particle size distribution and Inductively coupled plasma mass spectrometry (ICP-MS), and scanning electron microscopy (SEM). The XRD indicated that the sintered YSZ8 has a cubic structure. Total electrical conductivity of the sintered YSZ specimen was calculated in 700-900 °C and 0.21 ≤(pO2/atm)≤ 10−19 range by DC 4-probe method. The materials showed a maximum conductivity of 7.78 × 10−2 S.cm−1 at 900 °C with an activation energy of 0.83 ± 0.02 eV and the conductivity was lower than commercial 8YSZ at various temperature. The Hebb-Wagner polarization experiments were performed to measure partial electronic conductivity. The activation energies for conduction of holes and electrons were 1.48 ± 0.02 and 4.98 ± 0.94 eV, respectively. The electrolyte domain for YSZ8 was determined. © 2018, Hanyang University. All rights reserved.